Autonomy: A missing ingredient of a successful program? - Halperin, I.; Wulf, G.; Vigotsky, A.; Schoenfeld, B.; Behm, D. G. (Strength and Conditioning Journal, 2018)
Supporting an athlete's need for autonomy by allowing him/her to make choices concerning training variables can be an effective coaching strategy by strength and conditioning (s&c) professionals. However, this coaching strategy has received little attention in the s&c field despite being extensively studied in the fields of sport psychology and motor learning. Autonomy support has been shown to improve motor learning, performance, and motivation. In this review, the positive effects of providing choices are discussed as they apply to athletes and s&c professionals. Moreover, possible mechanisms for these effects are described and practical recommendations are provided.